Toxicidade aguda e risco ambiental dos antibióticos oxitetraciclina e florfenicol para o pacu (Piaractus mesopotamicus) - Carraschi, Silvia Patrícia [UNESP]; Shiogiri, Natália Sayuri; Venturini, Perri Francine; da Cruz, Claudinei [UNESP]; Gírio, Ana Cristina Fausto [UNESP]; Machado Neto, Joaquim Gonçalves [UNESP] (My University, 2011)
The oxytetracyline (OTC) and florfenicol (FLO) are the most used antibiotics for bacterial disease control in fish. The aims are: estimating the lethal concentration 50% initial (LC(I)50;48h) of OTC (Terramicina ®) and FLO (Aquaflor ®) for pacu (Piaractus mesopotamicus); classifying OTC and FLO according to the acute toxicity and the risk of environmental intoxication; and assessing OTC and FLO dilution effect in water quality variables. Fish were acclimatized for 10 days in a bioassay room at 27 ± 2 °C. Then nine animals (three each concentration) were exposed to 7.0; 7.5; 8.0 or 8.5 mg L -1 of OTC or to 600.0; 700.0; 800.0; 900.0 and 1000.0 mg L -1 of FLO and a control treatment. The water quality variables recorded daily were: pH, temperature, electric conductivity, and dissolved oxygen. OTC and FLO were classified according to acute toxicity and environmental risk. The estimated OTC LC(I)50;48h for pacu is 7.6 mg L -1 and the estimated FLO is > 1000 mg L -1. OTC reduced the dissolved oxygen concentration, and it was considered moderately toxic, causing risk of environmental intoxication to pacu. FLO is not toxic; it does not cause risk of environmental intoxication to pacu and does not change water quality variables.
Acute toxicity and environmental risk of oxytetracyline and florfenicol antibiotics to pacu (Piaractus mesopotamicus)
Keywords: Neotropical fish; Toxicity; Xenobiotic